2016
DOI: 10.1117/12.2223180
|View full text |Cite
|
Sign up to set email alerts
|

A next generation field-portable goniometer system

Abstract: Various field portable goniometers have been designed to capture in-situ measurements of a materials bidirectional reflectance distribution function (BRDF), each with a specific scientific purpose in mind. 1-4 The Rochester Institute of Technology's (RIT) Chester F. Carlson Center for Imaging Science recently created a novel instrument incorporating a wide variety of features into one compact apparatus in order to obtain very high accuracy BRDFs of short vegetation and sediments, even in undesirable conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…5. 9 In these experiments, individual variables such as grain size distribution and density were manipulated, along with the illumination geometry, and used in a series of laboratory biconical reflectance factor (BCRF) 7,8,10 measurements. The primary sites where field HCRF measurements were taken with GRIT in tandem with geotechnical measurements were on the western side of the Algodones Dunes system (Fig.…”
Section: Field Measurements Of the Angular Dependence Of Hyperspectralmentioning
confidence: 99%
See 1 more Smart Citation
“…5. 9 In these experiments, individual variables such as grain size distribution and density were manipulated, along with the illumination geometry, and used in a series of laboratory biconical reflectance factor (BCRF) 7,8,10 measurements. The primary sites where field HCRF measurements were taken with GRIT in tandem with geotechnical measurements were on the western side of the Algodones Dunes system (Fig.…”
Section: Field Measurements Of the Angular Dependence Of Hyperspectralmentioning
confidence: 99%
“…For the laboratory studies, BRDF measurements were conducted using two different generations of the goniometer system, GRIT 5,6 and GRIT-T. 9 In a laboratory setting, BRDF measurements are sometimes referred to as BCRF 7,8,10 measurements when there is a finite aperture for both the single directional illumination source and the sensor. The term "factor" signifies the referencing of sample radiance data to the radiance of a Lambertian standard.…”
Section: Laboratory Measurements Of the Angular Dependence Of Hyperspmentioning
confidence: 99%
“…A novel goniometer system capable of obtaining very high accuracy BRF measurements of vegetation and soils was recently developed in the Chester F. Carlson Center for Imaging Science, Rochester Institute of Technology [14], [15], known as the goniometer of the Rochester Institute of Technology-two (GRIT-T). The GRIT-T provides an important tool for studying the surface materials, such as sediments and the impact of their geophysical properties on spectral BRF.…”
Section: A Goniometer Of the Rochester Institute Of Technology-two: mentioning
confidence: 99%
“…Laboratory tests showed that the sensor has an elevation measurement repeatability within 0.5 mm and an elevation measurement accuracy within 2 mm. It was shown that the laser sensor has an elliptical beam spot size of approximately 11 mm × 4.5 mm when operating at a typical target-to-sensor distance of 600 mm [14], [15].…”
Section: A Goniometer Of the Rochester Institute Of Technology-two: mentioning
confidence: 99%
“…Another application is the characterization of surface albedo and vegetation patterns via satellite imaging. BRDF measurements at these size scales are typically done by goniometer-based setups, in which a light source and a detector are moved through a set of angles relative to a surface . At the sub-100 μm size scale of the work presented here, it is in principle possible to record BRDF measurements using goniometric ellipsometry setups (actually designed to determine the dielectric function of a material), but these typically suffer from a limited spatial resolution.…”
mentioning
confidence: 99%